Interactions Between Marine Group II Archaea and Phytoplankton Revealed by Population Correlations in the Northern Coast of South China Sea - Chen, Songze; Tao, Jianchang; Chen, Yufei; Wang, Wenxiu; Fan, Lu; Zhang, Chuanlun (Frontiers in Microbiology, 2022)
Marine Group II (MGII) archaea (Poseidoniales) are the most abundant surface marine planktonic archaea and are widely distributed in both coastal and pelagic waters. The factors affecting their distribution and activity are poorly understood. MGII archaea have the metabolic potential to utilize algae-derived organic matter and are frequently observed in high abundance during or following phytoplankton blooms, suggesting that they are key players of the marine food web. In this study, we studied interactions between MGII archaea and the diverse taxa of phytoplankton in the northern coast of South China Sea. Non-metric multidimensional scaling and cluster analyses demonstrated distinct MGII community patterns in the Pearl River plume (PRP) and the open regions of the northern South China Sea (ONSCS), with MGIIb dominating the former and MGIIa and MGIIb showing remarkable variations in the latter for the same sampling season. Nevertheless, positive correlations (Pearson correlation: R > 0.8 and P < 0.01) in absolute abundances of ribosomal RNA (rRNA)-derived complementary DNA and rRNA genes from network analyses were found between MGII archaea and phytoplankton (cyanobacteria, haptophytes, and stramenopiles in both PRP and ONSCS) among different particle size fractions, indicating their intrinsic relationships under changing environmental conditions. The results of this study may shed light on the multiple interactions between co-existing species in the micro-niches of different oceanic regions.